The Effect of Work Saturation (Burnout) on Employee Performance at PT. PLN (Persero) Makassar Transmission Implementation Unit - Mawaddah Warahmah; Bakhtiar Bakhtiar; Muhammad Luthfi Siraj (Public Resource Innovation Management and Excellence, 2025)
The impact of burnout on workers' performance in the Transmission Implementation Unit Makassar, PT. PLN (Persero). Conclusion. Study Program in Business Administration. Law and Social Science Faculty. University of Makassar. Under the direction of Muhammad Luthfi Siraj and Bakhtiar. This study sought to determine if staff performance at PT. PLN persereo) Transmission Implementation Unit Makassar was positively and significantly correlated with burnout. This study combines quantitative approaches with associative descriptive research, gathering data by observation, surveys, and recording. The sample for this study was derived from data processed using SPSS version 25, which included inferential analysis, descriptive and descriptive data analysis procedures, and validity and reliability tests. The study's findings show that there was no discernible relationship between staff performance and burnout at the PT. PLN (Persero) Transmission Implementation Unit Makassar. A validity test demonstrates that this is the case—it is higher than the table. Employee performance (Y) is 0.824% and rising burnout (X) is 0.951% according to the findings of a reliability test, indicating that each variable is to be dependent. The findings of a basic linear regression test show a correlation value of 0.045, indicating a very weak relationship between employee performance and burnout. The impact of burnout on employee performance at PT. PLN (Persero) Transmission Implementation Unit Makassar received a score of 1.1%, which is included in the very low category interval, according to the coefficient of determination of 0.011.